Change of ARASHI scores for large joints in rheumatoid arthritis patients treated with abatacept for three years: A clinical observational study - Takeshi MOCHIZUKI; Koichiro YANO; Katsunori IKARI; Ryo HIROSHIMA; Mina ISHIBASHI; Ken OKAZAKI (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate large joint damage progression using the assessment of rheumatoid arthritis by scoring of large joint destruction and healing in radiographic imaging (ARASHI) score in patients with rheumatoid arthritis (RA) treated with abatacept for three years. Patients and methods: A total of 71 consecutive patients with RA (7 males, 64 females; median age 68 years; range, 41 to 81 years) and joint lesions (141 shoulders, 139 elbows, 141 hips, 134 knees, and 142 ankles) treated with abatacept for three years were examined. Radiographic changes were assessed using the ARASHI score, and factors associated with radiographic progressive damage of large joints were analyzed using multivariate logistic regression. Results: The three-year radiographic progressive damage rates for the upper and lower limb large joints were 18.3% and 22.5%, respectively. Rates for the shoulder and knee decreased significantly (p=0.025 and 0.039, respectively), whereas rate for the ankle increased significantly (p=0.043). Multivariate logistic regression analysis identified the baseline ARASHI status score as an independent predictor of progressive damage of upper limb large joints within three years (p=0.004; odds ratio, 1.17). The cutoff value of the ARASHI status score for the upper limb large joints was 4, as determined from the receiver operating characteristics curve. No significant predictors of progressive damage were identified in the lower limb large joints within three years. Conclusion: The greatest suppression of the radiographic progressive damage of large joints was achieved for the shoulders and knees. Meanwhile, ankle damage progressed. Therefore, ankle joint damage should be monitored even in patients treated with abatacept. In the upper limbs, prescribing abatacept to patients with RA depending on their state of upper limb large joint damage may suppress damage progression.